Innovations In Mortgage-Backed Security Analytics: A Patent-Based Technology Review - Someshwar Mashetty (Kurdish Studies, 2022)
A Mortgage-Backed Security (MBS) is a type of asset-backed security that is secured by a collection of mortgages. As is common for the majority of securitized assets, investors are concerned with the risk and premium associated with MBS. The economic crisis was spearheaded by the burst of the housing bubble and the deteriorating of subprime mortgage performance. With the first increase in default rates, investors' perception of the risk associated with MBS drastically changed. Monitoring MBS performance and analyzing the quality of cash flows has become a necessary task for investors, pension funds, banks and other financial institutions. MBS performance depends on the quality of the underlying assets, i.e. the mortgages backing the securities. As with most structured finance products, the main cash flow risk is that of prepayment. Early payoffs, by either mortgage default and foreclosure or payment of mortgages' face value, usually occur during periods of falling interest rates and refinancing of existing higher-interest loans. Investors are therefore concerned with the timing of those cash flows, as well as MBS duration relative to other bonds. Due to the typical negative convexity associated with MBS, the performance is also non-monotonic with respect to movements in interest rates. This means that, other things being equal, longer duration MBS will outperform a given, shorter duration MBS when interest rates move down (up), provided the short MBS remains trading-rich (cheap).